2015
DOI: 10.1371/journal.pbio.1002194
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impairment Induced by Delta9-tetrahydrocannabinol Occurs through Heteromers between Cannabinoid CB1 and Serotonin 5-HT2A Receptors

Abstract: Activation of cannabinoid CB1 receptors (CB1R) by delta9-tetrahydrocannabinol (THC) produces a variety of negative effects with major consequences in cannabis users that constitute important drawbacks for the use of cannabinoids as therapeutic agents. For this reason, there is a tremendous medical interest in harnessing the beneficial effects of THC. Behavioral studies carried out in mice lacking 5-HT2A receptors (5-HT2AR) revealed a remarkable 5-HT2AR-dependent dissociation in the beneficial antinociceptive e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
166
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(175 citation statements)
references
References 94 publications
(120 reference statements)
8
166
0
1
Order By: Relevance
“…Specifically, we showed that TM5 and TM6 of D 1 R are implicated in the heteromerization of D 1 R and D 3 R [11]. Likewise, TM5 and TM6 of CB 1 Rs were found to be involved in the 5-HT 2A R-CB 1 R heteromer interface [52]. However, TM5 and TM1 of OX 1 R were involved in the CRF 1 R-OX 1 R heteromer interface [51].…”
Section: Clues To the Interfaces Involved In The A 2a R-d 2 R Heterotmentioning
confidence: 79%
See 1 more Smart Citation
“…Specifically, we showed that TM5 and TM6 of D 1 R are implicated in the heteromerization of D 1 R and D 3 R [11]. Likewise, TM5 and TM6 of CB 1 Rs were found to be involved in the 5-HT 2A R-CB 1 R heteromer interface [52]. However, TM5 and TM1 of OX 1 R were involved in the CRF 1 R-OX 1 R heteromer interface [51].…”
Section: Clues To the Interfaces Involved In The A 2a R-d 2 R Heterotmentioning
confidence: 79%
“…This technique is useful for determining which TMs are involved in the heterotetrameric interfaces. Recently, we successfully used this method to demonstrate the involvement of specific TM domains in the heteromerization of A 2A R and D 2 R [21], D 1 R and D 3 R [11], corticotropin-releasing factor CRF 1 (CRF 1 R) and orexin OX 1 receptors (OX 1 R) [51] and serotonin 5-HT 2A (5-HT 2A R) and cannabinoid CB 1 receptors (CB 1 R) [52]. In these studies, TMs of the receptors were fused to the HIV transactivator of transcription (TAT) peptide, allowing their effective insertion and orientation in the plasma membrane due to its capacity to penetrate it [11,21,51,53].…”
Section: Clues To the Interfaces Involved In The A 2a R-d 2 R Heterotmentioning
confidence: 99%
“…Evidence points also to ⌬ 9 -THC modulation of behaviors typically mediated by 5-HT 2A receptor activation (178, 305). Both in vitro and in vivo CB1 and 5-HT 2A receptors seem to form functionally active heteromers in specific brain regions, which seem to be required for some cognitive and anxiolitic effects of ⌬ 9 -THC, but not for antinociception and hypolocomotion (884).…”
mentioning
confidence: 99%
“…And it turns out that the receptor missing in McCormick's mice, 5-HT 2A , also interacts with CB 1 . When the team used a small peptide molecule to impede the 5-HT 2A and CB 1 interaction in normal mice, the same effect was seen 3 . He suggests that this could be a way to target the effects of cannabinoids more precisely.…”
Section: Precision Medicinementioning
confidence: 89%